Asymmetry and Parity Violation in Magnetoresistance of Magnetic Diluted Dirac–Weyl Semimetal (Cd0.6Zn0.36Mn0.04)3As2. Issue 12 (11th October 2018) - Ivanov, Oleg; Zakhvalinskii, Vasilii; Nikulicheva, Tatiana; Yaprintsev, Maxim; Ivanichikhin, Sergei
Abstract : Orientation dependences of magnetoresistance, ρ ( B → ), of single crystal (Cd0.6 Zn0.36 Mn0.04 )3 As2 having tetragonal P42 /nmc symmetry have been studied. Three orientations between electrical current, J →, flowing along crystal (100) plane and magnetic field, B →, have been used as follows: 1) B → is perpendicular to both J → and (100) plane; 2) B → is perpendicular to J → but parallel to (100) plane; 3) B → is parallel to both J → and (100) plane. Asymmetry in curves ρ ( B → ) is observed for all orientations. For orientation (2), crossover from negative to positive magnetoresistance is found as magnetic field changes its direction from one position corresponding to negative B → to opposite direction corresponding to positive B → . So magnetoresistance parity typical for numerous solids is violated for this orientation. The Shubnikov–de Haas (SdH) oscillations are observed for all orientations above ≈1.8 T and below ≈40 K. The effective mass of electrons extracted from SdH oscillations analysis is found to be orientation dependent. Smeared kinks correlated with the SdH oscillations are also observed in the Hall effect study for orientation (1). Magnetoresistance peculiarities can be related to specific properties of the Dirac semimetals and their evolution under magnetic field. Abstract : The orientation dependences of magnetoresistance for the (Cd0.6 Z0.36 Mn0.04 )3 As2 single crystal are measured at three various orientations between the electrical current flowing along crystal (100) plane and the magnetic field. For one measurement orientation, a crossover from positive to negative magnetoresistance occurs as the magnetic field is changed from initial positive direction to opposite negative one.